The Christmas Spirit - Macomber, Debbie (New York : Ballantine Books, 2022)
"Two lifelong friends, a bartender and a pastor, decide to trade places the week before Christmas and end up finding love along the way in this delightful novel from the queen of holiday stories, #1 New York Times bestselling author Debbie Macomber. Peter Rhinehart and Hank Meyer are best friends, but their lives couldnt be more different. Peter is a local pastor who is dedicated to his community. He spends his time visiting the flock, attending meetings, and with the holiday season approaching, preparing for the Christmas service and live nativity. As a bartender, Hank serves a much different customer base at his family-owned tavern, including a handful of lonely regulars and the local biker gang. When Peter scoffs that Hank has it easy compared to him, the two decide to switch jobs until Christmas Eve. To their surprise, the responsibilities of both bartender and pastor are similar, but much more difficult than either of them expected. As Peter and Hank begin to see one anothers lives in a new light, and each discovers a new love to cherish, their lives are forever changed. In The Christmas Spirit, Debbie Macomber celebrates the true meaning of the holidays and the inclusive community spirit that binds us all"--
Keywords: Friendship -- Fiction; Bartenders -- Fiction; Clergy -- Fiction; Motorcycle gangs -- Fiction; Christmas fiction